Childhood trauma levels in individuals attending adult mental health services: An evaluation of clinical records and structured measurement of childhood trauma. (June 2015) - Rossiter, Amy; Byrne, Fintan; Wota, Anna Paulina; Nisar, Zafar; Ofuafor, Thomas; Murray, Ivan; Byrne, Charles; Hallahan, Brian
Abstract: Despite an increased awareness regarding the prevalence and impact of childhood trauma, especially childhood sexual abuse (CSA), few studies examine the clinical reporting of such childhood experiences. This study compared the prevalence of childhood trauma recorded in individual's clinical notes to those ascertained with a structured validated questionnaire, examined which forms of childhood trauma were less likely to be reported to the treating mental health team and established which demographic or clinical factors were associated with reporting of childhood trauma. The prevalence of childhood trauma was ascertained using both the Childhood Trauma Questionnaire (CTQ) and a lifetime retrospective clinical note review in 129 individuals attending a general adult mental health service. Individuals were evaluated for the presence of mental health disorders, impulsivity, symptom severity and disability. Using the CTQ, childhood trauma was noted in 77% of individuals and recorded in 38% of individual's clinical notes ( p < 0.001). The greatest differences between CTQ reporting and clinical note documentation were noted for emotional neglect (62% versus 13.2%), physical neglect (48.1% versus 5.4%) and CSA (24.8% versus 8.5%). Childhood trauma was associated with increased psychopathology and greater symptom severity, and was particularly prevalent for individuals with personality disorders. This study demonstrated high rates of childhood trauma amongst adults attending a general adult mental health service. Furthermore, we demonstrated high rates of either non-enquiry from mental health professionals and/or high rates of non-documentation of childhood trauma by mental health professionals. Given the disparity between reporting of childhood trauma in clinical notes and findings with the CTQ, the use of a standardised questionnaire for the assessment of childhood trauma should be considered when performing a comprehensive mental health history.